Evaluation of the Nutritive Value of Air-Dried and Sun-Dried Sweet Potato (Ipomoea Batatas) Peels - P., Agubosi. O. C.; Dumkenechukwu, Imudia Favour; O, Alagbe. J. (European Journal of Life Safety and Stability (2660-9630), 2022)
This study was conducted to evaluate the nutritive value of sweet potato peels. The proximate composition, mineral composition, amino acid profile and anti-nutritional factors were determined in air-dried and sun-dried sweet potato peels. The sweet potato peels used for this research was collected from Gwagwalada and its environs. The results of the analysis show that crude protein (7.89%, 5.63%), crude fibre (3.41%, 3.68%), ether extract (1.71%, 2.15%), ash (6.95%, 5.82%), moisture (10.00%, 11.50%) and nitrogen free extract (70.04%, 71.22%) for air-dried and sun-dried sweet potato peels respectively. The air-dried and sun-dried peels had the following macro mineral contents respectively: calcium (61.70mg/100g, 45.73mg/100g), magnesium (9.33mg/100g, 5.11mg/100g), potassium (10.3mg/100g, 10.74mg/100g), sodium (4.12mg/100g, 1.52mg/100g), phosphorus (21.81mg/100g, 20.45mg/100g). The micro mineral content of zinc (1.00mg/100g) and iron (3.14mg/100g) in air-dried sweet potato peels had a higher value than that of sun-dried sweet potato peels. Sun-dried sweet potato peels had a higher value in copper (1.33mg/100g) and cobalt (0.18mg/100g) compared to the air-dried sweet potato peels. The air-dried and sun-dried sweet potato peels have the same manganese (1.22mg/100g) deposit in the mineral contents. A total of 16 amino acids (lysine, arginine, aspartic acid, threonine, histidine, serine, glycine, alanine, cystine, valine, leucine, phenylalanine, Tryosine, isoleucine, proline and methionine) were identified in the air-dried and sun-dried sweet potato peels, 9 of which were essential amino acid (lysine, arginine, threonine, histidine, valine, leucine, phenylalanine, isoleucine and methionine). The air-dried peels has the highest value of amino acids while sun-dried peels has the least except in Aspartic acid with 2.47% as compared to 2.13% air-dried peels, histidine with 6.18 % as compared to 4.71 % air-dried peels, alanine with 3.77% as compared to 3.13 % air-dried peels, valine with 1.10 % as compared with 0.88% air-dried peels and leucine with 2.79% as compared with 2.04 % air-dried peels. Histidine is the highest among the amino-acids with 6.18% in sun-dried sweet potato peels. The anti-nutritional factors detected includes: flavonoids, phenols, alkaloids, saponins, trypsin, phytate, cyanogenic glycosides, condensed tannins, hydrolysable tannins and anthocyanins. There is a reduction in the level of the nutritional factors after air-drying and sun-drying. Flavonoids in the air-dried peels was found to be above to be above the safe recommended level that should be consumed by animals. The data derived from the nutrient characterization of sweet potato peels in this study are clear indications that the sweet potato peels are rich in nutrients and can be used in feed formulation.